The recent similarity hypotheses to describe water infiltration into homogeneous soils (Scientia Agricola, 2016)
A similarity hypothesis recently presented to describe horizontal infiltration into homogeneous soils, developed for coarse-textured soils like sieved marine sand, implies that the soil water retention function θ(h) is the mirror image of an extended Boltzmann transform function θ(λ2). A second hypothesis applicable to vertical infiltration suggests that the soil water retention function θ(h) is also the mirror image of the soil water profile θ(z). Using previously published infiltration data, we investigated whether these two similarity solutions successfully describe infiltration into two “normal” soils. Although the theory using the first similarity assumption adequately describes horizontal cumulative infiltration and infiltration rate into both soils, it fails to estimate soil water distributions measured between soil profiles. The second similarity solution for vertical infiltration into either soil completely fails to coincide with measured soil water distributions, cumulative infiltration and infiltration rate.